Telaah Kritis Gaya Komunikasi Kang Dedi Mulyadi dalam Forum Musrenbang Berdasarkan Etika Hukum dan Komunikasi Islam - Azis, Pahrudin; Dermawan, Herman (Bayani, 2025)
This article critically examines Kang Dedi Mulyadi's communication style in the Musrenbang (Development Planning Forum) through the lenses of legal ethics and Islamic communication principles. The core issue addressed is the controversy surrounding his confrontational communication style toward formal institutions, raising concerns about ethical boundaries in public official discourse. The study aims to assess whether his communication aligns with the principles of good governance and Islamic values. Using a qualitative descriptive method with a normative-ethical and case study approach, data were collected from video documentation, speech transcripts, official responses from the DPRD, and public opinion. The findings reveal that Kang Dedi's communication style is populist and symbolic, effectively building emotional resonance with the public but risking violations of institutional ethics. From an Islamic perspective, while his communication reflects honesty and truthfulness, it requires balance through wisdom and responsibility to avoid counterproductive discord. The study concludes that a public official's communication must balance persuasive personal expression with institutional and ethical demands to remain constructive within a democratic framework.